2019
DOI: 10.1016/j.jocd.2018.05.039
|View full text |Cite|
|
Sign up to set email alerts
|

A Prospective Assessment of Periprosthetic Bone Mineral Density and Osteoimmunological Biomarkers Variations After Total Knee Replacement Surgery

Abstract: Aseptic loosening is a major cause of premature failure of total knee replacement (TKR). Variations in periprosthetic bone mineral density (BMD) and osteoimmunological biomarkers levels could help to quantify prosthesis osteointegration and predict early aseptic loosening. The gene expression of 5 selected osteoimmunological biomarkers was evaluated in tibial plateau bone biopsies by real-time polymerase chain reaction and changes in their serum levels after TKR were prospectively evaluated with enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A number of studies on THA and TKA found an increase in BMD at the tip of the implant but a notable decrease in the middle ROIs ( 40 , 41 ), and one found insignificant changes in BMD post-implantation ( 42 ). Interestingly, one study also found that a short stem implant resulted in significantly less BMD loss compared to a standard straight stem ( 43 ).…”
Section: Bmd Measurements For Oi In Amputeesmentioning
confidence: 99%
“…A number of studies on THA and TKA found an increase in BMD at the tip of the implant but a notable decrease in the middle ROIs ( 40 , 41 ), and one found insignificant changes in BMD post-implantation ( 42 ). Interestingly, one study also found that a short stem implant resulted in significantly less BMD loss compared to a standard straight stem ( 43 ).…”
Section: Bmd Measurements For Oi In Amputeesmentioning
confidence: 99%
“…Osteoblasts can also produce OPG, which acts as a decoy receptor, binding and blocking RANKL to inhibit osteoclasts activation and thus protect against bone loss [ 7 ]. Several studies have in fact proposed these new osteoimmunological biomarkers as useful tools in different conditions, for instance in assessing the progress of osteolytic bone metastases [ 7 ] or after total knee replacement surgery, to quantify the osteointegration of the prosthesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%